EFFECT OF WILD ABORTIVE CYTOPLASM INDUCING MALE STERILITY ON RESISTANCE / TOLERANCE AGAINST SIX RACES OF BACTERIAL LEAF BLIGHT IN SOME BASMATI RICE HYBRIDS - F. A. Faiz; M. Ijaz; M. Ahmad; S. I. Yasin; Q. D. Cruze; S. S. Virmani (Journal of Animal and Plant Sciences, 2008)
Three cytoplasmic male sterile (cms or A) lines and their maintainers (B) lines were used as testers and crossed with 17 restorers (R) lines to study the association of wild abortive (WA) cytoplasm with genetic vulnerability to six BLB races viz., PXO61, PXO86, PXO79, PXO71, PXO112, & PXO99. Significant variation was observed among R lines for all the BLB races. Tester variances were both significant and non-significant depending on the race or tester. Line x tester variances were significant in most cases except two, one in case of IR58025A & B against race 3 and one in case of IR68280A & B for race 2. The difference in mean lesion length in 46 A x R and B x R F1 crosses of IR70372A x restorers & IR70372B x restorers was negative & significant where as positive & significant difference in mean lesion length was observed in 42 A x R and B x R F1 crosses. Only 13 A x R F1 crosses showed non significant difference in mean lesion length when compared to their corresponding B x R F1 crosses. However, on over all basis the difference in mean reaction of A x R and B x R F1 crosses against six BLB races was significant for race 2, 3 & 6 and non-significant for race 1, 4 and 5. In case of IR58025A & IR58025B, difference in mean lesion length of 40 A x R and B x R F1 crosses of IR58025A x restorers & IR58025B x restorers was negative & significant difference where as positive & significant difference in mean lesion length was observed in 42 F1 crosses. In 15 cases the difference in mean lesion length of A x R and B x R F1 crosses was non significant. However, on over all basis, the difference in mean lesion length of A x R and B x R F1 crosses was negative & highly significant for race 5 only where as highly significant & positive difference was found for races 1, 2 &, 3 and non significant for two races; 4 & 6. Similarly in case of IR68280A & IR68280B, the difference in mean lesion length in 42 A x R and B x R F1 crosses of IR68280A & restorers and IR68280B & restorers was highly significant & negative where as positive & significant difference in mean lesion length was found in 29 A x R and B x R F1 crosses and non significant difference was observed only in 14 A x R and B x R F1 crosses. On over all bases, the difference in mean reaction of A x R and B x R F1 crosses of IR68280A & restorers and IR68280B & restorers was negative and highly significant for races 1, 3, & 4 and non-significant for races 2, 5 and 6. These results clearly indicate that the inconsistent behavior of all the three sets of A x R & B x R F1 crosses against six BLB races is suggesting nucleo-cytoplasmic interaction rather than the association of WA cytoplasm parental cms (A) lines with susceptibility to bacterial leaf blight races.
Keywords: Cms lines; Maintainer; Testers; Restorer; Wild abortive cytoplasm; Nucleo-cytoplasmic interaction and BLB